Social Media for Enhancing Stakeholders' Innovation Networks in Ontario, Canada. Issue 4 (2nd October 2018) - Kaushik, Pawandeep; Chowdhury, Ataharul; Hambly Odame, Helen; van Paassen, Annemarie
ABSTRACT: This case study assessed local food stakeholders' use of Facebook and Twitter to support interaction and build their networks of innovation in Ontario. Data were collected using Netlytic − an online data mining tool from the social media platforms − and key informant interviews. Findings revealed that stakeholders could be more innovative in their use of social media, but they would be unlikely to do so, without tapping into beneficial interactions of weak ties, as well as fostering strong ties. They also need to utilize the high brokerage role of key facilitating organizations and develop a social media strategy by integrating both 'online' and 'offline' interactions.